2022
DOI: 10.3389/fnins.2022.826759
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Volume Abnormality in Chronic Pain Patients With Depressive Symptoms: A Systemic Review and Meta-Analysis of Voxel-Based Morphometry Studies

Abstract: BackgroundGray matter volume (GMV) alteration in specific brain regions has been widely regarded as one of the most important neuroplasticity features in chronic pain patients with depressive symptoms (CP-D). However, the consistent and significant results were still lacking. Thus, further exploration was suggested to be performed.ObjectivesThis study aimed to comprehensively collect the voxel-based morphometry (VBM) studies on GMV alteration between CP-D and healthy controls (HCs). And a systemic review and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…in patients at baseline compared with HCs and also showed in MDDs before and after ECT, indicating that the superior frontal gyrus was an important area for the onset of depression and might be the area for the ECT response. Ma et al found decreased GMV in the medial part of the left superior frontal gyrus in patients with depressive symptoms (25), which was consistent with our results. Seok et al found decreased GMV in the right superior frontal gyrus in adolescents with irritability compared with healthy youths (26).…”
Section: Discussionsupporting
confidence: 93%
“…in patients at baseline compared with HCs and also showed in MDDs before and after ECT, indicating that the superior frontal gyrus was an important area for the onset of depression and might be the area for the ECT response. Ma et al found decreased GMV in the medial part of the left superior frontal gyrus in patients with depressive symptoms (25), which was consistent with our results. Seok et al found decreased GMV in the right superior frontal gyrus in adolescents with irritability compared with healthy youths (26).…”
Section: Discussionsupporting
confidence: 93%
“…The mechanisms underlying the simultaneous occurrence of mental health disorders and MSK pain are not fully understood, but are likely represented in a multidimensional manner, with genetics [ 47 , 48 ], physiology/neurobiology (e.g. brain structure alterations [ 49 ] and neurotransmitters [ 37 ]), and shared lifestyle–psychosocial factors [ 50–53 ] playing a part.…”
Section: Discussionmentioning
confidence: 99%
“…There are fewer amygdala connections with serotonergic projections in patients with chronic pain as well as with depression ( Zheng et al, 2022 ). Both concomitant states have been associated with global cortical gray matter volume alterations ( Ma et al, 2022 ). Furthermore, the two separate conditions may augment each other, worsening the states of both depression and chronic pain ( Surah et al, 2014 ).…”
Section: Pathophysiologymentioning
confidence: 99%